Peran Tuha Peut Gampong sebagai Mediator dalam Penyelesaian Sengketa Harta Warisan: (Studi di Gampong Neubok Badeuk Kecamatan Tangse Kabupaten Pidie) - Faiza, Nailul; Nazirah; Zalikha, Siti; Azzuhra, Rizki; Baitannur (Ameena Journal, 2022)
This study examines the role of Tuha Peut Gampong as a mediator in resolving inheritance disputes in Gampong Neubok Badeuk, Tangse District, Pidie Regency. Tuha Peut serves as a traditional institution and a deliberative body, functioning to mediate and reconcile community conflicts, including inheritance disputes. As a mediator, Tuha Peut does not make decisions but assists disputing parties in reaching an agreement through consensus. The research employs a qualitative method with a descriptive approach to explore the role of Tuha Peut in the mediation process. Primary data were collected from Tuha Peut members, supported by observations, interviews, and relevant documents. The findings reveal that Tuha Peut plays a significant role in restoring family ties that have been strained by inheritance disputes. The mediation process emphasizes impartiality and wisdom, encouraging all heirs to voluntarily reach a mutual agreement. This approach ensures that harmony and brotherhood among the disputing parties are maintained.